An analytical approach report system for construction cost control - a prototype development - Rathavoot Ruthankoon; Chotchai Charoenngam; Minato, Takayuki; Batanov, Dentcho N.; Asian Institute of Technology Partial Scholarship (Bangkok : Asian Institute of Technology, 1998)
The success of construction project management is to finish projects in time, cost and quality. The cost control system is a process that bring project to be finished within budgeted cost. Procedures of a cost control system include creating budget baseline, monitoring expenditures, analyzing variances, reporting cost status. A Report is one of the important sources of project information that give facilities for construction personnel to make decisions. Effective report cost control should have reliable support theories with effective analysis and direct hit information. An analytical approach report system is used as a criterion for the cost control. Cost and Schedule Control System Criteria concept are utilized for calculation in a cost control system, If-Then rules ideas is adopted for data analysis and highlighted process is for focusing out important problems. Because of these functions, analytical reports will be the system that provide meaningful management information. In this study, the structure of analytical report system was analyzed and designed. Operations of the system were transferred to physical objects by prototype development in form of computer applications. Adopted environment for developing is a kind of spreadsheet software called Microsoft Excel.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Construction industry -- Cost control